A New Decade in Banking (Canada The Canadian Bankers' Association, 1981)
This book reproduces the guest speakers' papers plus a synopsis of the exchanges that took place between the participants and the speakers.
Includes bibliographic references
osc 31/05/17
Loans
Keywords: Banks and banking, International; Banks and banking; International finance